Central and peripheral body fat distribution: Different associations with low-grade inflammation in young adults? - Cabral, Maria Bangdiwala (2021)
Background and aimsEvidence regarding the impact of regional body fat distribution on low-grade inflammation is limited. The current study examined the association of central and peripheral body fat distribution and low-grade inflammation levels in young adults, considering collinearity between variables.